2015
DOI: 10.1007/s00436-015-4480-5
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory and antiparasitic effects of garlic extract on Eimeria vermiformis-infected mice

Abstract: We investigated the immunomodulatory and parasiticidal effects of garlic extract on coccidiosis caused by Eimeria vermiformis infection in male ICR mice. One group received garlic extract daily until the end of the experiment by the oral route from 10 days prior to oral infection with 300 sporulated E. vermiformis oocysts (infected-garlic(+)). The other group served as a control positive with E. vermiformis infection alone (infected-garlic(-)). In the infected-garlic(+) group, garlic extract treatment induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…Des études ont même permis de comprendre le mécanisme d'action de certains composés isolés à partir des plantes utilisées en médecine traditionnelle vétérinaire (Sakkas et Papadopoulou, 2017). Les composés agissent notamment en renforçant le système immunitaire des animaux à travers la stimulation des macrophages ou en détruisant l'agent pathogène (Khalil et al, 2015). (Dharani et al, 2015).…”
Section: ■ Historique De La Medecine Ethnoveterinaireunclassified
“…Des études ont même permis de comprendre le mécanisme d'action de certains composés isolés à partir des plantes utilisées en médecine traditionnelle vétérinaire (Sakkas et Papadopoulou, 2017). Les composés agissent notamment en renforçant le système immunitaire des animaux à travers la stimulation des macrophages ou en détruisant l'agent pathogène (Khalil et al, 2015). (Dharani et al, 2015).…”
Section: ■ Historique De La Medecine Ethnoveterinaireunclassified
“…It has been shown that allicin has antibacterial and antifungal properties of potential medical importance (Borlinghaus et al 2014). Garlic extract as well as isolated secondary metabolites like propyl thiosulfinate oxide and propyl thiosulfinate have been shown to exhibit partial anticoccidial activity in vivo and in vitro (Kim et al 2013;Khalil et al 2015). In this study, efficacy of targeted allicin treatment on the development of chicken E. tenella sporozoites in cell culture was studied.…”
Section: Introductionmentioning
confidence: 99%
“…15 Garlic (Allium sativum L.), a typical traditional food with culinary and medicinal properties, is used for its antioxidant, anticancer, antimicrobial, antithrombotic, hypolipidemic, and hypoglycemic properties in traditional Chinese medicine. 16,17 Nillert et al reported that aged garlic extract has neuroprotective effects on improving cognitive dysfunction by mediating the neuroinflammation of Aβ-induced rats. 18 Epidemiological studies have reported a negative association with a variety of cancer types attributed to organosulfur compounds of garlic such as diallyl sulfide (DAS), diallyl disulfide (DADS), diallyl trisulfide (DATS), and volatile compounds found in garlic.…”
Section: Introductionmentioning
confidence: 99%